О применении Mathlab R206B для численного интегрирования нелинейных сингулярных задач Штурма-Лиувилля - Конкин Д. А. Дмитрий Анатольевич; Агеев Е. Ю. Евгений Юрьевич; Хатьков Н. Д. Николай Данилович; Литвинов Р. В. Рудольф Викторович (Радиотехника, 2008)
Заглавие с экрана